2023
DOI: 10.1021/acsami.2c20295
|View full text |Cite
|
Sign up to set email alerts
|

Shape Morphing by Topological Patterns and Profiles in Laser-Cut Liquid Crystal Elastomer Kirigami

Abstract: Programming shape changes in soft materials requires precise control of the directionality and magnitude of their mechanical response. Among ordered soft materials, liquid crystal elastomers (LCEs) exhibit remarkable and programmable shape shifting when their molecular order changes. In this work, we synthesized, remotely programmed, and modeled reversible and complex morphing in monolithic LCE kirigami encoded with predesigned topological patterns in its microstructure. We obtained a rich variety of out-of-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The LCEs can exhibit complex shape transformations by carefully programming the geometries and orientation patterns. Peng et al proposed an approach for realizing 4D printing of freestanding LCE by the integration of laser-assisted DIW and DLP, which provide design freedom and fabrication capability for applications. Wang et al prepared a photothermal composite ink AuNR/LCE and demonstrated that 3D-printed AuNR/LCE flower whose petals can be “bloomed” globally or individually.…”
Section: Introductionmentioning
confidence: 99%
“…The LCEs can exhibit complex shape transformations by carefully programming the geometries and orientation patterns. Peng et al proposed an approach for realizing 4D printing of freestanding LCE by the integration of laser-assisted DIW and DLP, which provide design freedom and fabrication capability for applications. Wang et al prepared a photothermal composite ink AuNR/LCE and demonstrated that 3D-printed AuNR/LCE flower whose petals can be “bloomed” globally or individually.…”
Section: Introductionmentioning
confidence: 99%
“…Hillel et al 43 used an approximate numerical method to calculate local LCE deformation curvature, achieved programmable arbitrary LCE three‐dimensional shape deformation, and created a 3D “Robot face”. Chen et al 44 proposed LCE kirigami with topological patterns and implemented different functionalities, such as a bioinspired fluttering butterfly, a flower bud, dual‐rotation light mills, and dual‐mode locomotion. Based on the principles of muscles, Mengqi et al 45 enabled programmable LCE muscles to achieve diverse motions through the cooperative actions of otherwise simple contraction/expansion of individual muscle bundles.…”
Section: Introductionmentioning
confidence: 99%